THE POLITICAL INTERVENTION ON GOVERNMENT OFFICIALS’ PROMOTION IN INDONESIA - Wargadinata, Ella Lesmanawaty (Universitas Padjadjaran, 2024)
The promotion government officials comes into new era, the new policy reversed from a very closed selection process and heavily seniority-based to open, clear criteria, transparent procedures on the competency-based series test. In fact, policy implementation is not fully in favour of an administration driven. The study has two main research problems “How open promotion for local government officers conducted?” and “How does political intervention work in the open promotion mechanism?”. This paper provides comprehensive mechanism-the hybrid administration-politics model on open promotion of local bureaucrats in Indonesia. The study used a qualitative approach and assited by Nvivo 12 to reveal the most frequent concept on open promotion practices based on interviews. The data obtained through interviews with informants which selected purposively, selection committee members, candidates, and local government officers. This paper affirms interesting features. The competency series tested by independent assessors reflects an administration mechanism through merit concept. However, the absolute political final decision-making process at the governor or Mayor’s hands reflects the individual-political interest. This system shows that the administration’s process at the local level links tightly to political deliberation. The key message is that open promotion in government agencies is neither a pure merit issue nor a spoils system for competence-heavy based, on the one hand, yet is always amenable to some political intervention. The merit principles are universal; however, the practices are contextual-specific. This study has an important value in describing how The politics play significant role on local administration system.